2011
DOI: 10.1002/pmic.201000768
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprobe‐based immobilized metal affinity chromatography for sensitive and complementary enrichment of multiply phosphorylated peptides

Abstract: Magnetic nanoparticles (MNP, <100 nm) have rapidly evolved as sensitive affinity probes for phosphopeptide enrichment. By taking advantage of the easy magnetic separation and flexible surface modification of the MNP, we developed a surface-blocked, nanoprobe-based immobilized metal ion affinity chromatography (NB-IMAC) method for the enhanced purification of multiply phosphorylated peptides. The NB-IMAC method allowed rapid and specific one-step enrichment by blocking the surface of titanium (IV) ion-charged n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The cations are immobilized on metal ion chelation groups, such as nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), or phosphate polymer, which are on the surface of agarose-, silica-, or magnetic-based solid supports. 3941 MOAC, similar to IMAC, uses the affinity of metals in metal oxide particles (TiO 2 , ZrO 2 , Fe 3 O 4 , etc.) to retain the anionic phosphoryl groups on the matrixes.…”
Section: Enrichment Techniquesmentioning
confidence: 99%
“…The cations are immobilized on metal ion chelation groups, such as nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), or phosphate polymer, which are on the surface of agarose-, silica-, or magnetic-based solid supports. 3941 MOAC, similar to IMAC, uses the affinity of metals in metal oxide particles (TiO 2 , ZrO 2 , Fe 3 O 4 , etc.) to retain the anionic phosphoryl groups on the matrixes.…”
Section: Enrichment Techniquesmentioning
confidence: 99%
“…NPs employed for selective enrichment of phosphopeptides by IEX have included unmodified Fe 3 O 4 mNPs and Fe 3 O 4 mNPs modified with PEI . NPs for selective enrichment of phosphopeptides by IMAC have been prepared by immobilization of N ′, N ″‐ bis (carboxymethyl)‐ l ‐lysine (NTA) on Fe 3 O 4 /SiO 2 core/shell mNPs modified with either 3‐(2‐aminoethyl)aminopropyltrimethoxysilane or 3‐aminopropyltriethoxysilane, respectively . Magnetic NPs for MOA have been prepared almost exclusively from Fe 3 O 4 /SiO 2 core/shell (silica encapsulated Fe 3 O 4 ) mNPs and include (i) Fe 3 O 4 /TiO 2 core/shell mNPs , (ii) Fe 3 O 4 /carbon/TiO 2 (carbon encapsulated Fe 3 O 4 ) core/shell mNPs , (iii) Fe 3 O 4 /SiO 2 /ZrO 2 core/shell mNPs , (iv) Fe 3 O 4 /SiO 2 core/shell mNPs coated with aluminum oxide , (v) Fe 3 O 4 /SiO 2 core/shell mNPs coated with zirconium phosphonate , and (vi) Fe 3 O 4 /SiO 2 core/shell mNPs‐coated tantalum oxide .…”
Section: On‐target and Nanoparticle‐facilitated Enrichment Of Phosphomentioning
confidence: 99%
“…23 The double phosphopeptides accounted for about 10% of the total identified phosphopeptides and the rest of the phosphopeptides identified by using the three materials were in highly phosphorylation. Although the distributions of phosphopeptides according to the number of phosphorylation sites are similar for the three materials, it was extensively reported that different materials have complementary performance towards phosphopeptides enrichment, 14,23,37 thus, it is of great interest to investigate the overlap of the identified phosphopeptides by the three materials. As predicted in Fig.…”
Section: Detection Limit Of Phosphopeptides From Tryptic B-casein Digmentioning
confidence: 99%
“…Despite the advance of these mentioned IMAC materials, some difficulties are still encountered. Due to the different surface properties and metal ligand complexes of IMAC materials, many acidic nonphosphopeptides are strongly bound to the magnetic supports 37,39 and the binding capacity of phosphopeptides still remains limited, which would result in low sensitivity and specificity. On the other hand, these reports highlighted that suitable surface modification of the magnetic supports is of great research demand to enhance the efficiency of phosphopeptide capture.…”
Section: 25-30mentioning
confidence: 99%